Excellent intrinsic long‐term thermal stability of co‐evaporated MAPbI₃ solar cells at 85 °C - Dewi, Herlina Arianita (2021)
Thermal stability is a critical criterion for assessing the long‐term stability of perovskite solar cells (PSCs). Here, it is shown that un‐encapsulated co‐evaporated MAPbI3 (TE_MAPbI₃) PSCs demonstrate remarkable thermal stability even in an n‐i‐p structure that employs Spiro‐OMeTAD as hole transport material (HTM). TE_MAPbI3 PSCs maintain over ≈95% and ≈80% of their initial power conversion efficiency (PCE) after 1000 and 3600 h respectively under continuous thermal aging at 85 °C. TE_MAPbI₃ PSCs demonstrate remarkable structural robustness, absence of pinholes, or significant variation in grain sizes, and intact interfaces with the HTM, upon prolonged thermal aging. Here, the main factors driving TE_MAPbI₃ stability are assessed. It is demonstrated that the excellent TE_MAPbI₃ thermal stability is related to the perovskite growth process leading to a compact and almost strain‐stress‐free film. On the other hand, un‐encapsulated PSCs with the same architecture, but incorporating solution‐processed MAPbI3 or Cs0.05(MA0.17FA0.83)0.95Pb(I0.83Br0.17)3 as active layers, show a complete PCE degradation after 500 h under the same thermal aging condition. These results highlight that the control of the perovskite growth process can substantially enhance the PSCs thermal stability, besides the chemical composition. The TE_MAPbI₃ impressive long‐term thermal stability features the potential for field‐operating conditions.